ASSOCIATION OF ARTERIAL STIFFNESS WITH ALL-CAUSE MORTALITY AMONG HOSPITALIZED COVID-19 PATIENTS. (April 2021) - Rodilla, Enrique; Belda, Alberto; Canales, Sergio; Quilis, Maria; Saez, Maria Carmen; Roldan, Alicia; Cortes, Xavi; Aguilar, Marta; Albert, Amparo; Garijo, Marta; Malek, Tamara; Palop, Marta; et al.
Abstract : Objective: Older age and cardiovascular comorbidities are well-known risk factors for all-cause mortality in COVID-19 patients. Hypertension (HT) and age are the two principal determinants of arterial stiffness (AS). The objective of this study is to estimate AS in COVID-19 patients requiring hospital admission and analyze its association with all-cause mortality. Design and method: This cross-sectional, observational, retrospective multicenter study includes 122170 patients who required hospital admission in 150 Spanish centers, included in the nationwide SEMI-COVID-19 Network. We compared estimated AS as pulse pressure > 60 mmHg and compared clinical characteristics between survivors and nonsurvivors. Results: Mean age was 67.5 ± 16.1 years, 42.5% were women. Most patients were white (90.0%). Globally, 2606 (21.4%) subjects died. Blood pressure (BP) < 120 mmHg and BP > 140 at admission predicted higher all-cause mortality (23.5% and 22.8%, respectively, p < 0.001), compared to BP between 120–140 mmHg (18.6%). 4379 patients with AS (36.0%) were older and had higher systolic and lower diastolic BP. Multivariate analysis showed that even adjusting for gender (males, OR: 1.6, p = 0.0001), age tertiles (second and third tertiles, OR: 2.0 and 4.7, p = 0.0001), Charlson-Index (second and third tertiles, OR: 4.8 and 8.6, p = 0.0001), heart failure, previous and in-hospital antihypertensive treatment, AS and BP < 120 mmHg significantly and independently predicted all-cause mortality (OR: 1.27, p = 0.0001 and OR: 1.48, p = 0.0001, respectively). Figure. No caption available. Conclusions: Our data show that arterial stiffness, defined as pulse pressure above 60 mmHg at hospital admission, and BP at admission < 120 mmHg were important determinants with independent prognostic value for all-cause mortality in COVID-19 patients requiring hospitalization.